A cross-sectional study of ECG patterns and outcomes of patients thrombolysed for ST-elevation myocardial infarction at a district, public Cape Town hospital - Kibamba, Crispin Ngoy (Division of Emergency Medicine, 2019)
Introduction There is insufficient data to describe ST-elevation myocardial infarction (STEMI) in sub-Saharan African settings using common diagnostic criteria. This study describes the outcomes at discharge (survival, death or transferred) of patients thrombolysed for STEMI at a public hospital without primary percutaneous coronary intervention capability as well as associated ECG changes. Materials and methods A retrospective, cross- sectional study was conducted at an urban, public emergency centre in Cape Town, South Africa that did not have direct access to percutaneous coronary intervention for STEMI. Descriptive statistics for age, length of stay and the various timings surrounding thrombolysis were presented using proportions, mean and standard deviation. Assumptions were tested using the X2 - test or Fishers Exact test. A p-value less than 0.05 was considered significant. Results The study enrolled 104 patients of which 25 were excluded for insufficient data and two for thrombolysis of an incorrect STEMI diagnosis. Of the remaining patients, 56 (64%) survived to discharge, 26 (30%) required transfer and five (6%) died. There was no difference between regions affected and patient outcome (p=0.31). Resolution of ST-segments was seen in 48 (86%) survivors. It was not seen in 21 (81%) who were transferred and in none that died. The difference between resolution of ST-segments between survivors versus those transferred or dead was highly significant (p< 0.001). Conclusion This study described a higher than expected thrombolysis failure rate as well as a higher than expected association of poor outcome with inferior STEMI. It highlights the need for improved health care records to improve health research in low-resourced settings. The creation of a STEMI registry could contribute to research but will need funding. The use of clinical messaging apps to gain senior ECG interpretation may provide an additional layer toward quality care.